2016
DOI: 10.1016/j.infbeh.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Semantics guide infants’ vowel learning: Computational and experimental evidence

Abstract: Semantics guide infants' vowel learning: computational and experimental evidenceter Schure, S.M.M.; Junge, C.M.M.; Boersma, P.P.G. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Since this seminal study (Maye et al., ), there have been several studies evidencing that the shape of frequency distributions guides categorization, yet all focused on (auditory) phoneme acquisition (e.g., Maye, Weiss, & Aslin, ; ter Schure, Junge, & Boersma, ; Yoshida, Pons, Maye, & Werker, ). It thus remains an open question whether infants employ this learning mechanism also outside the spoken language domain, that is, whether it serves as a domain‐general cue.…”
mentioning
confidence: 99%
“…Since this seminal study (Maye et al., ), there have been several studies evidencing that the shape of frequency distributions guides categorization, yet all focused on (auditory) phoneme acquisition (e.g., Maye, Weiss, & Aslin, ; ter Schure, Junge, & Boersma, ; Yoshida, Pons, Maye, & Werker, ). It thus remains an open question whether infants employ this learning mechanism also outside the spoken language domain, that is, whether it serves as a domain‐general cue.…”
mentioning
confidence: 99%
“…After applying the inclusion criteria, there were 13 papers that could be considered for a quantitative meta-analysis, from a variety of sources: 6 journal articles (Liu & Kager, 2014;Maye et al, 2002Maye et al, , 2008ter Schure, Junge, & Boersma, 2016;Wanrooij et al, 2014;Yoshida et al, 2010), 1 article in proceedings (Liu & Kager, 2011), 1 chapter in a collection (Capel, De Bree, De Klerk, Kerkhoff, & Wijnen, 2011), 1 unpublished manuscript (Cristia, 2011), and 4 sets of data that had not been included in public written reports but had been presented at conferences as posters or talks (Fennell, Hudon, & Spring, 2012;Pons, Mugitani, Amano, & Werker, 2006;Pons, Sabourin, Cady, & Werker, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned in the Introduction, it has been proposed that infants could (additionally) exploit prelexical, lexical and/or multimodal learning strategies when learning about the sound categories in their native language, and some of these proposals are even supported their own proof-of-principle experiments (ter Schure et al, 2016;Feldman et al, 2013). Supposing that further research along these lines confirms the robustness and reliability of such early results, future work could assess whether multiple such approaches may be fruitfully combined, or whether at certain ages or in certain situations, infants solely exploit a subset of such sound category learning strategies.…”
Section: Theoretical Implications For Phonological Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forms around peaks in this distribution are then perceived as being a distinct category. Recent computational models showed that infant-directed speech contains sufficiently clear peaks for such a distributional learning mechanism to succeed and also that top-down processes like semantic knowledge and visual information play a role in phonetic category learning (ter Schure et al, 2016).…”
Section: Phoneme Perceptionmentioning
confidence: 99%